Scott Lash, Bronislaw Szerszynski y Brian Wynne (eds.), Risk Evironment & Modernity, Londres, Sage Publications, 1996. - Lezama, José Luis (Estudios Demográficos y Urbanos, 1998)
Scott Lash, Bronislaw Szerszynski y Brian Wynne (eds.), Risk, Environments Modernity, Londres, Sage Publications, 1996.